Effects of DHA and Tualang honey on the brain cytokines following chronic stress exposure in rat model - Zulkaflee, Mohd Hazim; Asari, Mohd Asnizam; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Mohd Yusof, Nurul Aiman (Penerbit Universiti Sains Malaysia, 2020)
Objectives: Exposure to chronic stress has been shown to affect various inflammatory cytokine in the brain. Previous studies suggested that docosahexaenoic acid (DHA) and Tualang honey (TH) can provide some protection against the negative effects of chronic stress to our body. Therefore, the aim of the present study was to experimentally assess the protective effects of DHA, TH and their combination (DHATH) on the activity of inflammatory cytokines in the brain of rats following exposure to chronic stress. Methods: Fifty male Sprague-Dawley rats aged 6 weeks old were divided into five groups: (i) control; (ii) stress exposed; (iii) DHA treated (900 mg/kg body weight twice daily via oral gavage); (iv) TH treated (2.0 g/kg body weight twice daily via oral gavage) and (v) combined DHATH treated. Except the control, all other groups received stress regimen which consisted of combination of restraint stress and force swimming stress test for 28 days. Selected inflammatory cytokines, TNF-α, IL-6 and IFN-γ in brain homogenates were measured using ELISA method. Results: Concentration of TNF-α, IL-6 and IFN-γ in the DHA treated, TH treated and combined DHA-TH treated group were significantly lower when compared to the stress exposed group (P < 0.05). However, there is no statistical difference between combined DHA-TH and DHA-treated and TH-treated groups Conclusion: Consumption of DHA and TH may be effective in lowering brain inflammatory cytokines under chronic stress condition. However, combining these two substances would not reduce the cytokines level even further than taking either of them alone.